Hydrodynamic voltammetry with channel microband electrodes: Axial diffusion effects - Alden, J; Compton, R (1996)
The strongly implicit procedure is used to simulate the response of channel electrodes under conditions where diffusional effects in the direction (axis) of solution flow are significant. The cases of flow rate dependence of the steady-state transport limited current, potential step transients and ECE processes are considered and the conditions identified under which axial diffusion effects are considerable.